Multiple spacecraft coordination and motion planning for full-coverage inspection of large complex space structures. (January 2023) - Faghihi, Sepideh; Tavana, Siavash; de Ruiter, Anton H.J.
Abstract: This paper presents a new multiple spacecraft full-coverage inspection path-planning scheme to closely observe any large complex space structure hovering in space. For this purpose, a decentralized multi-spacecraft methodology is proposed, extending our previous work on the inspection of structures using a single inspector spacecraft for a cooperative collection of small spacecraft. Multi-robot systems are more reliable, flexible, and scalable and can accomplish complex missions, which might be impossible or significantly time-consuming for a single robot. To this end, our previously developed asymptotically optimal sampling-based path planner, called the Rapidly Exploring Random Tree, is combined with a multi-spacecraft coordination methodology. The resulting kinodynamic inspection path planner generates 3-dimensional inspection trajectories for each spacecraft to fully observe any points on the boundary of a complex space structure in close proximity while satisfying the kinematic and dynamic constraints. Spacecraft coordination, communication, and task allocations are developed to reduce the total inspection time, crucial during servicing and proximity operations. Simulation results are presented to demonstrate the ability and effectiveness of our planner. Highlights: Multi-spacecraft coordination and motion planning for inspection of large space structures. Decentralized coordination for cooperative and homogeneous collection of small spacecraft. Full sensor coverage inspection trajectories for complete inspection of the space structure. Contributing to the technologies required for space exploration and proximity operations.